The Influence of Calcium Ions on the Electrotransfer Efficiency of Plasmid DNA and Cell Viability - Rūta Palepšienė; Martynas Maciulevičius; Paulius Ruzgys; Baltramiejus Jakštys; Saulius Šatkauskas (Applied Sciences, 2023)
Gene electrotransfer (GET) is recognized as a promising technique for the development of an efficient tool for gene therapy. Such a therapy would have applications in the treatment of a variety of genetic diseases, including cancer. However, despite its wide applicability, the technique is limited by the lack of understanding of the fundamental mechanism of electroporation as well as other important factors that directly or indirectly influence its success rate. In the current study, we analyzed the impact of low concentrations (0–1 mM) of Ca2+ on the process of DNA electrotransfer using flow cytometry. The results revealed that the presence of a CaCl2 concentration as low as 0.25 mM decreased the efficiency of GET by ~1.5-fold and cell viability decreased by ~2–3-fold. In addition, we determined that the observed phenomenon of the decrease in pDNA electrotransfer due to the influence of Ca2+ was not the consequence of cell death but rather should be attributed to secondary mechanisms. The data presented in this study provide an insight into the importance of Ca2+ in the process of gene electrotransfer that may be directly applicable to in vivo settings.